Climate warming in the Qinghai-Tibet Plateau and Mongolia as indicated by air freezing and thawing indices. (May 2022) - Wu, Tonghua; Zhu, Xiaofan; Wang, Pengling; Adiya, Saruulzaya; Avirmed, Dashtseren; Dorjgotov, Battogtokh; Li, Ren; Wu, Xiaodong; Lou, Peiqing
Highlights: The warming magnitudes of air temperature were summarized in the QTP and Mongolian on seasonal and annual scales. The spatio-temporal changes of air freezing and thawing indices were characterized in the QTP and Mongolia. The changes of air freezing and thawing indices could imply that the difference of warming characteristics in the QTP and Mongolia. The changes of air freezing and thawing indices indicate that climate warming have great influence on the permafrost. Abstract: The majority of the Qinghai-Tibet Plateau (QTP) and Mongolia are underlain by permafrost. We have examined trends in air temperature and associated freezing/thawing index by using a non-parametric statistical method for the QTP and Mongolia from 1961 to 2011. The annual air temperature and associated freezing/thawing index exhibit similar patterns, suggesting similar warming trend in the two regions. The annual warming trends of air temperature are 0.33 °C/decade and 0.37 °C/decade in the QTP and Mongolia, respectively. The freezing index show significantly decreasing trends with −56.7 °C·days/decade and −57.5 °C·days/decade, while the thawing index present obvious increasing trends of 68.2 °C·days/decade and 68.3 °C·days/decade in the QTP and Mongolia, respectively. We find that the variations of air temperature and freezing/thawing index exhibit prominent spatial heterogeneity, and the warming trends is attributed to different seasonal warming. The warming trends in the QTP are dominated by winter warming, it is coincide with previous studies. Contrary to the QTP, autumn warming mainly accounts for the warming trends in the Mongolia. In addition, a winter cooling trend is observed in the Mongolia during the last two decades. These findings will be helpful to better understand the spatial heterogeneity of permafrost changes.